Youthsites : histories of creativity, care, and learning in the city - Poyntz, Stuart R. (Social justice and youth community practice, 2023)
This book is an original study of youth organizations in London, Toronto, and Vancouver that represent a burgeoning global sector of creative and cultural learning for socially marginalized young people. The book is also about a sector that is not recognized as such—organizations that do not like being institutionalized, forms of education that exist outside the mainstream, types of aesthetic expression that often go unrecognized, and opportunities for socially marginalized young people who are frequently denied them. Rooted in the history of community arts movements from the 1970s, YouthSites or the non-formal youth arts learning sector is now part of cities throughout the world. Technological change, shifts in educational discourses, changes in policy rhetorics, including a turn away from traditional public institutions, and a corresponding decline in confidence and funding of formal public schooling have all impacted the growth of youth arts organizations. Yet, there are currently no systematic studies of the history, structure, and development of this sector. This book fills this gap and is the first book to develop an internationally comparative, evidence-based, structural analysis of the development of the youth arts sector. Based on an original 4-year study examining the history, priorities, and tensions within this sector between 1995 and 2015, this book explores the new creative transition routes, organizations, and people who help young people become creators, citizens, or just themselves at a time when support for young people seems to be perilously fragile or at risk.